Social Elements of Dialects in Oum El Bouaghi: Survey Study - Fadloun, Zohra (Indonesian Journal of Social Science Research, 2025)
This research aims at determining the social elements of the variety of dialects in eastern Algeria's Oum El Bouaghi Region. We used we used field study, a descriptive method, to achieve the goal, the field study was in the Department of Social Sciences at Oum El Bouaghi University, we selected 50 students from the branch of Sociology specialty. The results showed that Oum El Bouaghi city has a variety of dialects according to many social elements like: social communication cultural heritage, marriage between individuals from different regions, the harsh geography of the city makes a harsh tone of sounds among people, The harsh geographical area, which generates a harsh dialect, the nature of dialect itself, social class, work, demise of some social values.